Evaluasi Kegiatan Sub Bagian Data dan Informasi Pada Gugus Tugas COVID 19 di Kabupaten Tulungagung - Ratih Cahyaning Tyas (Universitas Airlangga, 2022)
Background: Coronavirus Disease 19, commonly dubbed as COVID-19, has been widely spread across the globe since March 2020, and WHO has declared it a Pandemic. In Indonesia, the disease began to spread in June 2020. The spreading rate was so fast that it reached every part of the country, including the Tulungagung district in East Java. The Government of Tulungaggung has tried to curb the rapid spread of COVID-19 cases by establishing the